(untitled) (Research, Society and Development, 2020)
The juca is a common plant in northeastern Brazil, has its known antioxidant capacity and proven therapeutic power. However, there is little information about its use as an antioxidant bioadditive in soybean oil. Thus, the antioxidant efficacy of the aqueous and hydroalcoholic extracts of the juca was investigated, through analysis in vitro (by total phenolic compounds, antioxidant activity by free radical scavenger method - DPPH and by iron reducer method – FRAP), and in vivo (by oil with juca extracts, monitoring its oxidation during a 90-days). Hydroalcoholic extracts from juca showed greater oxidative stability than aqueous extracts. The hydroalcoholic extracts of the juca showed high levels of phenolic compounds (166.59 mgEAG / g of fruit and 179.55 mgEAG / g of stem bark), and high antioxidant activities by the methods of DPPH and FRAP, at the end of 90 days. The in vivo investigations indicated that the formulation of hydroalcoholic extract with 0.85% of the fruit and 0.85% of the stem bark showed a greater protective effect against the increase of the peroxide index in the soybean oil, showing that the simultaneous use of the additives have synergistic antioxidant effect. Therefore, juca hydroalcoholic extracts can be used as an antioxidant bioadditive in soybean oil.